Feasibility and acceptability of wrist-worn actigraphy to measure frailty in homebound older adults - Lindsey F Lin; Justin Mutter; Karen Duffy; Meghan K Mattos (Digital Health)
Background/Objectives Frailty assessments in older adults are an important prognostic indicator for predicting health-related outcomes. The purpose of this study was to determine the feasibility and acceptability of using a wrist-worn actigraphy device to measure frailty in homebound older adults. Methods In this US single-site cohort study, older adult participants were asked to continuously wear an actigraphy device on their wrist for three weeks. Caregivers were asked to complete short descriptive surveys. Surveys collected demographic and subjective frailty measures; sleep and activity data were collected via Actiwatch. Descriptive statistics were performed for quantitative data; qualitative analyses were conducted for open-ended survey questions. Results Twelve of the thirteen dyads completed all study activities, participants demonstrated feasibility and acceptability of device use, and dyads reported overall positive experiences. Conclusion Findings suggest that wearing a wrist-worn actigraphy device is feasible and acceptable in homebound older adults and can potentially measure objective frailty over time.